Gazing Into Language Development: Exploring Individual Variability in Early Word Recognition in Infancy Through Eye‐Tracking. - Gerbrand, Anton; Wengman, Johan; Forssman, Linda (Infancy)
Previous research suggests that early word recognition is an important foundation for subsequent vocabulary development. However, the optimal method for assessing this ability in infancy remains unclear. To investigate this issue, we collected data from 70 participants (45.7% female) at 10, 11.5, 18 and 24 months of age using two eye‐tracking based tasks—the preferential looking‐ and mismatch paradigms—as well as parental reports on a short form of the Swedish Early Communicative Development Inventories (SE‐CDI). Both eye‐tracking‐based paradigms correlated with concurrent and later vocabulary scores. However, while the preferential looking paradigm showed stability across time, the mismatch paradigm did not demonstrate longitudinal stability and its associations with vocabulary were sometimes in unexpected directions. These findings suggest that the mismatch paradigm may reflect shifting cognitive or attentional processes during development, highlighting the need for further investigation. In contrast, the eye‐tracking based preferential looking paradigm, may offer an objective complement to parental reports for predicting subsequent vocabulary development in early childhood.